2020
DOI: 10.1002/ejsp.2664
|View full text |Cite
|
Sign up to set email alerts
|

A social psychological perspective on World War II collaboration in the 21st century: A Belgian case

Abstract: On the night of May 8-9, 1945, after a first signature on May 7 in Reims, German and Allied military representatives signed the capitulation of the Third Reich. This act marked the end, on the western front, of the deadliest war of the twentieth century: World War II (WWII). While the time had come for popular celebrations among the winners, the purge of those who had collaborated with the Germans was on its way. Belgium, which was liberated by the allies a few months earlier, was no exception. Indeed, 0.64% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Alongside a national perspective, community dynamics coexist that develop alternative narratives of the past centered on the history of the community members (Liu et al, 2021). These alternative narratives exist side by side with the national memory, leading here and there to a set of frictions (Bouchat et al, 2020). They provide alternative 'prisms' for interpreting national interests in crisis.…”
mentioning
confidence: 99%
“…Alongside a national perspective, community dynamics coexist that develop alternative narratives of the past centered on the history of the community members (Liu et al, 2021). These alternative narratives exist side by side with the national memory, leading here and there to a set of frictions (Bouchat et al, 2020). They provide alternative 'prisms' for interpreting national interests in crisis.…”
mentioning
confidence: 99%
“…Yet, studies have shown repeatedly that WWII is still seen as one of the most (if not the most) critically important event in recent history, regardless of respondents' age (Bobowik et al, 2014;Liu et al, 2009;Schuman & Scott, 1989). If collective remembering of historical events can have major impacts on groups and individuals in terms of identity (Assmann & Czaplicka, 1995;Liu & Hilton, 2005), political attitudes and preferences (Bouchat et al, 2020;Rimé, Bouchat, Klein, & Licata, 2015), and their interpretation of the world around them (Schuman & Rieger, 1992), it is crucial to understand what different generations know about the war as they continue to list it as a historically important event.…”
mentioning
confidence: 99%